Effects of a competitive season on body composition in female intercollegiate athletes - Williams, S. T. (My University, 1995)
This study was designed to compare body composition over the course of a season in several intercollegiate women's athletics teams. Four basketball (BB) players, 18 cross country (CC) runners, 9 gymnasts (GYM), 10 swimmers (SW) , and 7 volleyball (VB) players from the University of Wisconsin-La Crosse, an NCAA ~ivision 111 school, volunteered for the study. Body composition was determined through hydrostatic weighing, and a questionnaire examining the desire to lose or gain weight and aerobic activity pattern was given at the beginning and end of each athletic season. Using a 2-way mixed design ANOVA with repeated measures, the statistical analysis of the body composition variables showed the GYM and SW significantly (p < .05) decreased percent body fat over the course of their seasons. At the early season, CC runners and GYM had significantly (p < .05) less body weight and fat weight (FW) than VB players, SW, and BB players. CC runners also had significantly (p < .05) less fat-free weight (FFW) than all other teams. VB players had significantly (p < .05) greater FFW than the GYM and SW, whereas the BB players only had significantly (p < .05) greater FFW than the gymnasts. Late season differences were the same as early season differences with the exceptions that the BB players no longer had significantly (p > .05) greater FFW than GYM, nor significantly (p > .05) greater FW than the cc runners. The results of the study suggest that body composition among athletic teams varies, which may be a result of the unique training techniques and expertise required for different sports. Further research should involve the evaluation of body composition and its relation to athletes and their performance.
Keywords: Body composition; College sports - Physiological aspects; Sports for women - Physiological aspects